2014
DOI: 10.1136/emermed-2013-203340
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of lateral neck radiography in ruling out supraglottitis: a prospective observational study

Abstract: UMIN000011928.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Because six studies of the eight included studies used the two‐gate study design, the patient selection domain and flow and timing domain had a high risk of bias and of invalid applicability. In five of the eight studies included, the index test was interpreted without the results of the reference standard . Due to the nature of the research, laryngoscopic evaluation was carried out after the index test.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because six studies of the eight included studies used the two‐gate study design, the patient selection domain and flow and timing domain had a high risk of bias and of invalid applicability. In five of the eight studies included, the index test was interpreted without the results of the reference standard . Due to the nature of the research, laryngoscopic evaluation was carried out after the index test.…”
Section: Resultsmentioning
confidence: 99%
“…Fujiwara et al . prospectively enrolled 105 adult patients who had undergone lateral neck radiographs to evaluate supraglottitis . One radiologist and one emergency physician, who were blind to patients’ symptoms and laryngoscopic evaluations, interpreted lateral neck radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Kurashiki Central Hospital is an urban hospital with 1172 beds that serves 800,000 people in the western area of Okayama Prefecture, Japan. 10 This study was conducted and reported in accordance with the statement of the Japanese Society for Pharmacoepidemiology and the Standards for Reporting of Diagnostic Accuracy Studies criteria. [11][12][13] The study was approved by the institutional review board of Kurashiki Central Hospital and the Research Institute of Healthcare Data Science.…”
Section: Methodsmentioning
confidence: 99%
“…9 Lateral soft tissue cervical X-ray examination is also easy to be performed on children, approximately 83% if compared to CT scan examination. 10 Flexible fiberoptic laryngoscopy as the gold standard examination of larynx is not always available in all hospitals, and the high cost of the examination inspires the researchers to conduct a comparison of lateral soft tissue cervical X-ray examination with flexible fiberoptic laryngoscopy examination on patients of LPR with LTH, with expectation that it could be used as a reference for assessment and diagnostic support. The researchers believe that the X-ray examination could be useful in providing an overall view towards LTH manifestations, therefore, an LTH diagnosis could be made based on radiological examination.…”
Section: Introductionmentioning
confidence: 99%